A Bcool spectropolarimetric survey of over 150 solar-type stars. Issue Volume 9:Issue S302(2013) (7th August 2014) - Marsden, Stephen; Petit, Pascal; Jeffers, Sandra; do Nascimento, Jose-Dias; Carter, Bradley; Brown, Carolyn
Abstract: As part of the Bcool project, over 150 solar-type stars chosen mainly from planet search databases have been observed between 2006 and 2013 using the NARVAL and ESPaDOnS spectropolarimeters on the Telescope Bernard Lyot (Pic du Midi, France) and the Canada France Hawaii Telescope (Mauna Kea, USA), respectively. These single "snapshot" observations have been used to detect the presence of magnetic fields on 40% of our sample, with the highest detection rates occurring for the youngest stars. From our observations we have determined the mean surface longitudinal field (or an upper limit for stars without detections) and the chromospheric surface fluxes, and find that the upper envelope of the absolute value of the mean surface longitudinal field is directly correlated to the chromospheric emission from the star and increases with rotation rate and decreases with age.